2023
DOI: 10.1111/gcb.16618
|View full text |Cite
|
Sign up to set email alerts
|

Response of nitrate leaching to no‐tillage is dependent on soil, climate, and management factors: A global meta‐analysis

Abstract: No tillage (NT) has been proposed as a practice to reduce the adverse effects of tillage on contaminant (e.g., sediment and nutrient) losses to waterways. Nonetheless, previous reports on impacts of NT on nitrate (NO −3 ) leaching are inconsistent. A global meta-analysis was conducted to test the hypothesis that the response of NO − 3 leaching under NT, relative to tillage, is associated with tillage type (inversion vs non-inversion tillage), soil properties (e.g., soil organic carbon [SOC]), climate factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 128 publications
1
5
0
Order By: Relevance
“…This study was conducted during the second and third years of no-tillage cultivation, during which nitrogen leaching levels in no-tillage were observed to be higher compared to conventional tillage practices. These findings align with the data collected by Li and colleagues [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study was conducted during the second and third years of no-tillage cultivation, during which nitrogen leaching levels in no-tillage were observed to be higher compared to conventional tillage practices. These findings align with the data collected by Li and colleagues [22].…”
Section: Discussionsupporting
confidence: 92%
“…Ref. [22] demonstrated that, the response of NO 3 − -N leaching is closely tied to soil attributes like Soil Organic Carbon (SOC), climatic factors (particularly water input), and management practices like the duration of no-tillage (NT) and nitrogen fertilizer input. Significantly, SOC emerges as the key factor influencing the risk of NO 3 − -N leaching under NT conditions.…”
Section: Introductionmentioning
confidence: 99%
“…During periods with lower rainfall (10,11,20, and 21, Figure 2), the unfertilized plots exhibited significantly higher NO 3 − leaching than those fertilized (Tables 5 and 6). NO 3 − leaching in no-tillage areas without fertilization has already been reported by Rosolem et al [38], who evaluated the phenomenon in these situations over a year without rainfall restrictions and found NO 3 − concentrations of up to 111 mg L −1 .…”
Section: Discussionmentioning
confidence: 96%
“…In addition, corn provides a large amount of plant residues for soil cover, and soybean fixes atmospheric N. Regardless of these positive aspects, the continuous implementation of soybean-corn rotation subverts one of the fundamental principles of the no-tillage system, which is the diversification of plant species through crop rotation [16,17]. Despite controversies and only a few conclusive studies on the subject, long-term no-tillage with diversified crop rotation (cover crops and commercial species) is considered a soil management system with lower NO 3 − loss through leaching than conventional management [18][19][20][21]. However, studies on NO 3 − leaching in long-term no-tillage systems that compare diversified and simplified cropping rotations under subtropical agricultural conditions are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Last, nitrate nitrogen leaching can be an important mechanism in regulating soil pH [58]. Thus, a no-tillage-induced increase in nitrate nitrogen leaching [59] can be an important cause of potential soil acidification under no-tillage conditions. However, the positive effect of no-tillage on nitrate nitrogen leaching declined with increasing initial soil organic carbon [59].…”
Section: No-tillage Effectsmentioning
confidence: 99%